P674 Ustekinumab is the preferred biological agent in IBD patients with hidradenitis suppurativa failing anti-TNF therapy : results from a real-life multicenter cohort. (30th January 2023) - Verstockt ., B; Vieujean, S; Truyens, M; Julsgaard, M; Pugliese, D; Aslan, D; Prokopic, M; Lim, S; Viganò, C; Festa, S; Ramos, L; Garciá, M J; et al.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, recurrent inflammatory disease affecting skin that bears apocrine glands and is characterised by painful, deep-seated, inflamed lesions. Treatment includes antibiotics, steroids, surgery, and adalimumab as the only approved biological agent. An association between inflammatory bowel disease (IBD) and HS has been reported, but very limited evidence exists on the efficacy of non-anti-TNF biological agents for the treatment of HS in IBD patients. Methods: This multicenter case series was performed as part of the Collaborative Network of Exceptionally Rare case reports (CONFER) project by ECCO. Cases of patients with HS and IBD treated with non-anti-TNF biological agents were retrospectively collected through a standardised collection form. Efficacy measures were reported by the local gastroenterologist/dermatologist using physician global assessment (PGA). Results: Fifty-five patients (65.5% women, median [IQR] age 40.0 [33.1-47.6] years, 50.9% active smokers) were identified (Table 1), all with HS diagnosis confirmed by a dermatologist. We observed a strong CD predominance (90.9%) in the current cohort. HS affected mainly the inguinal (82.0%) and axillary (76.0%) regions, followed by the anogenital region (46.0%). In 42 patients, HS was diagnosed a median of 10.0 [4.3-16.4] years after the IBD diagnosis, whereas in 13 HS preceded the IBD diagnosis by 4.1 [2.2-5.4] years. Prior to initiating a non-anti-TNF biological agent, all patients had been exposed to at least 1 anti-TNF agent, including (high dose) adalimumab in 83.2% of the cases. In 20% of patients, HS developed while being treated with an anti-TNF agent. After anti-TNF failure (for either IBD and/or HS), physicians opted for ustekinumab (83.6%), vedolizumab (14.5%), or risankizumab (1.8%) as the preferred first non-anti-TNF agent. During ustekinumab treatment (n=46, median time on therapy 2.1 [0.8-3.3] years)), 76.1% showed a clinically relevant HS improvement (including 50.0% complete remission), whereas 23.9% did not experience any benefit. With vedolizumab (n=8), 37.5% experienced some benefit (including 25.0% with complete remission), while 62.5% did not report any improvement. The single patient on risankizumab had complete remission. Finally, 6 out of 8 vedolizumab-treated patients were ultimately treated with ustekinumab, reporting a clinical benefit in 5 out of 6. Conclusion: Ustekinumab is the preferred biological agent after anti-TNF failure in IBD patients with concomitant HS. Although placebo-controlled trials are lacking and ustekinumab is not approved for the treatment of HS, the current multi-centre case series demonstrates a substantial benefit in 78.4% of patients.